Evaluation of relative content and crystallization behavior of homogeneous crystals in poly (lactic acid) by terahertz spectroscopy. (27th March 2023) - Zhu, Zhenqi; Yu, Zelin; Bian, Yujing; Zhang, Xun; Zeng, Ruonan; Yang, Bin
Abstract: Poly (lactic acid) (PLA) is a typical polymer with homogeneous polymorphism. Its different crystal forms have their own crystallization paths, which endow it with special properties. Therefore, it is crucial to study the structure and crystallization behavior of PLA to better understand its properties. Here, we investigate PLA films obtained under different crystallization conditions by terahertz (THz) spectroscopy. The α′, α and their mixed crystal forms of PLA exhibit completely different spectral feature. Based on the frequency of THz characteristic peaks, we further determine the relative contents of α′ form and α form in PLA with mixed crystals, the validity of which is verified by comparing X-ray diffraction (XRD). Furthermore, the change of absorption intensity of different PLA films is significantly different with crystallization time, mainly manifested as the change rate of glassy PLA crystallized at 80 °C is faster than that of molten PLA. We believe that this is because the crystallization of the α form of PLA at 80 °C is at a disadvantage, which reduces the speed of conformational adjustment. The results show that THz spectroscopy can not only characterize the crystal changes of polymers, but can also be an effective method to study the kinetics of polymer crystallization. Graphical abstract: Image 1 Highlights: The α′, α and their mixed forms of PLA exhibit different spectral feature in the THz band. The content of homogenous crystals in PLA is quantitatively evaluated by THz spectroscopy. At THz frequencies, the crystallization behavior of α′ and α in PLA is observed.